Effect on blood lipids of two daily servings of Camembert cheese. An intervention trial in mildly hypercholesterolemic subjects. (December 2014) - Schlienger, Jean-Louis; Paillard, Francois; Lecerf, Jean-Michel; Romon, Monique; Bonhomme, Cécile; Schmitt, Bernard; Donazzolo, Yves; Defoort, Catherine; Mallmann, Cécilia; Le Ruyet, Pascale; Bresson, Jean-Louis
Abstract As a concentrated source of saturated fat, cheese consumption is considered to be associated with increased cholesterolemia and generally forbidden in dietary guidelines for adults with hypercholesterolemia. The aim of this study was to evaluate the impact of saturated fatty acids on lipid parameters and blood pressure with regards to different types of dairy products: Camembert and full-fat yoghurt. One-hundred and fifty-nine moderate hypercholesterolemic subjects without treatment were instructed to consume two full-fat yoghurts (2 × 125 g) per day for 3 weeks (run-in period) and then for a further period of 5 weeks, either two full-fat yoghurts or two 30 g servings of Camembert cheese per day. We observed that over the 5-week daily consumption of two servings of Camembert cheese, blood pressure and serum lipids did not change in moderate hypercholesterolemic subjects. These results suggest that fermented cheese such as Camembert could be consumed daily without affecting serum lipids or blood pressure.